2021
DOI: 10.1590/1983-21252021v34n410rc
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Attractors and Traps for Capture of Spotted-Wing Drosophila in Vineyards1

Abstract: Pest monitoring is a practice that enables the estimation of populational density of insect-pests in crops. However, it requires the use of attractors and traps that present high efficiency. The objective of this work was to evaluate the efficiency of food attractors using different trap models for the capture of spotted-wing drosophila (Drosophila suzukii) insects, and the capture selectivity of these models in vineyards of Cabernet Sauvignon. The experiment was conducted in the 2018-2019 crop season, in São … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…D. suzukii uses visual signals to orient itself at long distance and olfactory stimuli at short distance (Cha et al, 2012;Little et al, 2019). Although several commercial products exist for the capture of D. suzukii, their efficacy and selectivity are highly variable depending on the crop and the time of the season (Brilinger et al, 2021;Larson et al, 2021;Whitener et al, 2022).…”
Section: Behavioral Manipulationmentioning
confidence: 99%
“…D. suzukii uses visual signals to orient itself at long distance and olfactory stimuli at short distance (Cha et al, 2012;Little et al, 2019). Although several commercial products exist for the capture of D. suzukii, their efficacy and selectivity are highly variable depending on the crop and the time of the season (Brilinger et al, 2021;Larson et al, 2021;Whitener et al, 2022).…”
Section: Behavioral Manipulationmentioning
confidence: 99%
“…However, the efficacy of mass trapping depends strongly on the attractiveness of the lure used (Lee et al, 2013). A study conducted in Cabernet Sauvignon vineyards in the highland area of Santa Catarina state, testing a combination of traps and food attractants, showed that the attractive Droskidrink (red wine, apple cider vinegar, and sugar), provided the highest capture rates of D. suzukii (Brilinger et al, 2021).This was the same attractant that we used in Chapters II and III. This food attractant proved also to have the lowest non-target effects and selective against hymenopteran and coleopterans.…”
mentioning
confidence: 67%
“…Females of D. suzukii can infest and cause damage to fruits in ornamental, wild, and economically important fruit trees (Mitsui, Beppu, & Kimura, 2010;Poyet et al, 2014). In Brazil, during the past decade, D. suzukii has already been detected in southern and southeastern regions, in peach orchards (Prunus persica) (Foppa et al, 2018), apple (Malus domestica) (Oliveira, Amaral Neto, & Santos, 2015) and vineyards (Vitis vinifera) (Brilinger, Arioli, Werner, Rosa, & Boff, 2021). It was also identified infesting strawberry fruits (Fragaria x ananassa) (R. S. S. dos Santos, 2014;Wollmann et al, 2020), blueberry (Vaccinium myrtillus) (Vilela & Mori, 2014), feijoa (Acca sellowiana) (Souza et al, 2017), papaya (Carica papaya), guava (Psidium cattleianum) (Wollmann et al, 2020;Zanuncio-Junior et al, 2018), blackberry (Rubus spp.)…”
mentioning
confidence: 99%